2015
DOI: 10.1016/j.jmva.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence assessment in censored mixed-effects models using the multivariate Student’s-tdistribution

Abstract: In biomedical studies on HIV RNA dynamics, viral loads generate repeated measures that are often subjected to upper and lower detection limits, and hence these responses are either left- or right-censored. Linear and non-linear mixed-effects censored (LMEC/NLMEC) models are routinely used to analyse these longitudinal data, with normality assumptions for the random effects and residual errors. However, the derived inference may not be robust when these underlying normality assumptions are questionable, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The use of censored regression models like censReg allowed for the accounting of censoring at 0 and 40 min and an unbiased estimation of sex differences. Similar methods have been used to assess risk in drug toxicity studies and human immunodeficiency virus studies (Matos et al, 2015;Berges et al, 2018).…”
Section: Mixed and Fixed Model Analysesmentioning
confidence: 99%
“…The use of censored regression models like censReg allowed for the accounting of censoring at 0 and 40 min and an unbiased estimation of sex differences. Similar methods have been used to assess risk in drug toxicity studies and human immunodeficiency virus studies (Matos et al, 2015;Berges et al, 2018).…”
Section: Mixed and Fixed Model Analysesmentioning
confidence: 99%
“…To assess the influence of minor perturbations on the maximum likelihood estimate trueθ^ for incomplete data problems, Zhu & Lee () proposed the use of the Q ‐displacement functionfQfalse(bold-italicωfalse)=2trueQ^)(bold-italicθfalse^trueQ^)(trueθ^bold-italicωand the associated influence graphαfalse(bold-italicωfalse)=bold-italicωfQfalse(bold-italicωfalse).Following the approach of Cook () and Zhu & Lee () (see also Matos et al . ), we use the normal curvature CfQ,-0.166667emboldd of α ( ω ) at ω 0 in the direction of some unit vector d to summarise the local behavior of f Q ( ω ). It can be shown thatCfQ,d=2dtrueQ¨ωodandtrueQ¨ω0=boldΔbold-italicω0}{trueQ^¨false(trueθ^false)1boldΔω0,wheretrueQ^¨false(trueθ^false)=2θbold-italicθ...…”
Section: Diagnostic Analysismentioning
confidence: 99%
“…Following the approach of Cook (1986) and Zhu & Lee (2001) (see also Matos et al 2015), we use the normal curvature C f Q ,d of (ω) at ω 0 in the direction of some unit vector d to summarise the local behavior of f Q (ω). It can be shown that…”
Section: Local Influencementioning
confidence: 99%
“…However, and from a practical standpoint, such an assumption may not be realistic. In fact, some recent works on censored models (see for example, Matos et al 2013Matos et al , 2015Garay et al 2017a, b) have indicated that likelihood-based inference can be seriously affected by the presence of atypical observations and/or misspecification of the parametric distributions for both random effects and errors.…”
Section: Introductionmentioning
confidence: 99%